2022
DOI: 10.2147/ccid.s363583
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices in Hyaluronic Acid Dermal Filler Treatment in Asia Pacific and Practical Approaches to Achieving Safe and Natural-Looking Results

Abstract: Complications such as delayed inflammatory reactions (DIRs) and unnatural outcomes can sometimes arise from hyaluronic acid (HA) dermal filler treatments and can be challenging to address. Given the popularity of HA dermal fillers for aesthetic procedures, there is a need for preventive strategies to minimize these complications. Two hundred practitioners from 10 regions in Asia Pacific who administer HA fillers completed a survey on prevention of DIRs and unnatural outcomes. Thirteen global experts convened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hyaluronic acid fragments below 1000 kDa are proinflammatory and can initiate an inflammatory response by activating Tolllike receptors 2 and 4 [31]. Some studies have suggested that the Vycross technology hyaluronic acid filler may have a higher risk of delayed inflammatory reactions because of its low-molecular-weight hyaluronic acid composition [32]. However, although hyaluronic acid fillers usually contain a high-molecule hyaluronic acid, it is degraded by hyaluronidase and reactive oxygen into 20-kDa fragmants [7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronic acid fragments below 1000 kDa are proinflammatory and can initiate an inflammatory response by activating Tolllike receptors 2 and 4 [31]. Some studies have suggested that the Vycross technology hyaluronic acid filler may have a higher risk of delayed inflammatory reactions because of its low-molecular-weight hyaluronic acid composition [32]. However, although hyaluronic acid fillers usually contain a high-molecule hyaluronic acid, it is degraded by hyaluronidase and reactive oxygen into 20-kDa fragmants [7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 30 Some studies have suggested that the Vycross technology hyaluronic acid filler may have a higher risk of delayed inflammatory reactions because of its low-MW hyaluronic acid composition. 31 However, although hyaluronic acid fillers usually contain a high-MW hyaluronic acid, it is degraded by hyaluronidase and reactive oxygen into 20-kDa fragments. 7 Thus, it is reasonable to assume that the periphery of the implanted hyaluronic acid filler can be degraded by hyaluronidase and that low-MW fragments of hyaluronic acid could induce an inflammatory response.…”
Section: The Hyaluronic Acid Fillermentioning
confidence: 99%
“…[10][11][12] Panels of experts have defined key strategies to achieve naturallooking results when injecting HA fillers: patient assessment and individualisation of treatment plan, adequate knowledge of facial anatomy, proper injection techniques, good knowledge of the rheological properties and behaviours of different HA fillers, and a conservative treatment approach. 13,14 Patients are not only looking to improve their appearance, but also their mental and emotional health, along with social wellbeing. 15 In a survey on patient motivations to undergo cosmetic procedures, psychosocial concerns were mentioned more than other identified themes, specifically the appeal for improved confidence, feeling depressed and anxious with current appearance, and feeling consumed by efforts to conceal undesirable physical features.…”
mentioning
confidence: 99%